Marine Biofilms: A Successful Microbial Strategy With Economic Implications - de Carvalho, Carla C. C. R. (Frontiers in Marine Science, 2018)
Bacteria and other microorganisms have evolved an ingenious form of life, where they cooperate and improve their chances of survival when subjected to environmental stress, called biofilms. In these communities of adhered cells, bacteria are protected by a matrix of extracellular polymeric substances that provide protection against e.g. temperature and pH fluctuations, UV exposure, changes in salinity, depletion of nutrients, antimicrobial compounds and predation. Their success in marine environments and the number of bacterial cells in the sea, allow them to colonize nearly all man-made surfaces in contact with seawater. The costs to maritime transport, aquaculture, oil and gas industries, desalination plants and other industries are significant which has led to the development of various strategies to prevent biofilm formation and cleaning of infected surfaces. In this review, the benefits for bacterial cells to live in biofilms and the consequences to human activities are discussed.